The role of my style (CPM / PERT) in enhancing the performance of construction projectsAn Empirical Study in the Department of projects in the office of the province of Baghdad - داود, فضيلة سلمان; حسين, زينب هادي (Journal of Economics and Administrative Sciences, 2016)
AbstractThis study was to demonstrate the role-use planning scientific methods is disabled and little used in the planning and follow-up construction of vital projects in the province of Baghdad, including network planning methods, in order to find the optimal time to finish the project in light of the resources available and the budget set for it, in the current research has been used the most prominent network planning methods and two stylistic (CPM / PERT), was the application of the critical path method on standard-design school project (traditional) to draw Action Network according to confirmed times for the activities of the project and account his Crashing time , It was Pert technique applied to the project hematology center in dignity Teaching Hospital - Baghdad, draw Action Network according to the "three times (optimistic, pessimistic and most likely") own technology as a result of conditions is confirmed that surrounds the circumstances of the implementation of the project, And find the critical path and determine how long speculative to complete the project and the cost of speculative, with the ratio calculated the probability of completion of the project, was used ready-made computer programs in ways that networking planning to process the data and get the results and draw retinas projects respondents, and programs It was used (MS Project, Win-QSB) , The study showed that for the application of my style (CPM / PERT) a major role in providing the most important project resources, a "time", and his consequential of the rationalization of costs, while providing alternatives and provide the perfect solution for trade-off between time and cost of a school project, and indicate the possibility of ending the project blood disease center within the period Selected according to his work Bert network, and this researcher recommended the beneficiary of activating the role of planning research using networking planning methods and it is important for their role in the implementation and follow-up performance boost construction.